Volcanic Risk Mitigation that Could Have Been Derailed but Wasn’t: Pinatubo, Philippines 1991 - Newhall, Chris (Frontiers in Earth Science, 2021)
This is the story of a successful hazard mitigation effort at Mount Pinatubo in 1991 that could easily have failed. The counterfactuals are the myriad of ways that the effort could have failed but didn’t. Forecasts for a large, VEI 6 eruption were the basis of 10, 20, 30 and, during the climactic eruption, even 40 km radius evacuations. Let’s use the metaphor of a train headed for the destination of successful mitigation, but that could have easily have been derailed or slowed and shunted off to a siding. Among the possible waystations of derailment: capability and trust between responding institutions; external distractions, both natural and man-made; early alert; scientific judgment of whether, when, and how big an eruption will occur; stochastic or unpredictable factors that can make even the best scientific judgment moot; optimal balance between caution and decisive actions, by scientists and civil defense alike; and effective communication between all parties. Potential derailments are detailed at each of these waystations for Pinatubo.